Manajemen Organisasi Dalam Mendorong Kemandirian Organisasi Kemahasiswaan dan Mahasiswa di STIE Kalpataru - Ali Rahman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to obtain information on the extent to which good organisational management will be able to encourage independence for student organisations at STIE Kalpataru. A strong and resilient organisation will also indirectly encourage the independence of students who are members and administrators of the student organisation. So that with more quality and capacity that is owned in addition to the academic ability produced by the students concerned. The research was conducted using the literacy study method with the development of information and data from field studies.